Diagnostic Accuracy of Combined Acetylcholinesterase Histochemistry and Calretinin Immunohistochemistry of Rectal Biopsy Specimens in Hirschsprung's Disease. (September 2018) - Jeong, Hasong; Jung, Hye Ra; Hwang, Ilseon; Kwon, Sun Young; Choe, Misun; Kang, Yu Na; Jung, Eunyoung; Kim, Sang Pyo
Background. Acetylcholinesterase (AchE) histochemistry has been established as an accurate diagnostic tool for Hirschsprung's disease (HD). In addition, calretinin immunohistochemistry is also reported as a reliable and adjunctive method to diagnose HD. We investigated the diagnostic value of combined AchE histochemistry and calretinin immunohistochemistry in rectal suction biopsies from HD and non-HD patients. Methods. We retrospectively reviewed 99 rectal suction biopsy specimens including 4 repeat biopsies from 95 patients (34 HD and 61 non-HD). Each specimen was evaluated with hematoxylin-eosin, AchE histochemistry, and calretinin immunohistochemistry. Results. Of 95 patients, only 21 (22.1%) showed some ganglion cells. All 61 non-HD cases revealed no abnormal AchE-positive fibers. Of 34 HD patients, 32 exhibited abnormal AchE fibers, but 2 showed no stained fibers. None of the tissues from the HD patients exhibited calretinin immunoreactivity. Test sensitivity and specificity of AchE histochemistry alone were 93.5% and 100.0%, respectively, while calretinin immunohistochemistry were 100.0% and 85.2%, respectively. Conclusions. AchE histochemistry is a good diagnostic method for HD, if feasible, and a combination of AchE histochemistry and calretinin immunohistochemistry will help increase the accuracy of the diagnosis of HD.